In-vitro antimicrobial activity screening of some ethnoveterinary medicinal plants traditionally used against mastitis, wound and gastrointestinal tract complication in Tigray Region, Ethiopia - Kalayou, Shewit (Asian Pacific Tropical Medicine Press, 2012)
OBJECTIVE: To screen the antibacterial activity of nine ethnoveterinary plants traditionally used for the treatment of mastitis, wound and gastrointestinal complications. METHODS: Hydroalcoholic exctracts of medicinal plants namely, Achyranthes aspera (A. aspera) L. (Family Asparagaceae), Ficus caria (F. caria) (Family Moraceae), Malvi parviflora (M. parviflora) (Family Malvaceae), Vernonia species (V. species) (local name Alakit, Family Asteraceae), Solanum hastifolium (S. hastifolium) (Family Solanaceae), Calpurinia aurea (C. aurea) (Ait) Benth (Family Fabaceae), Nicotiana tabacum (N. tabacum) L. (Family Solanaceae), Ziziphus spina-christi (Z. spina-christi) (Family Rhamnaceae), Croton macrostachys (C. macrostachys) (Family Euphorbiaceae), were screened against clinical bacterial isolates of veterinary importance from October 2007 to April 2009. The antibacterial activity was tested using disc diffusion at two concentrations (200 mg/mL and 100 mg/mL) and broth dilution methods using 70% methanol macerated leaf extracts. RESULTS: With the exception of S. hastifolium all plant extracts exhibited antibacterial activity. Among the medicinal plants tested C. aurea, C. macrostachyus, A. aspera, N. tabacum and vernonia species (Alakit) showed the most promising antimicrobial properties. CONCLUSIONS: It can be concluded that many of the tested plants have antibacterial activity and supports the traditional usage of the plants for mastitis, wound and gastrointestinal complications treatment. Further studies into their toxicity and phytochemistry is advocated.